Optimization Method for Cross-Regional Scheduling of Retired Charging Pile Component Reuse - Yuan Wang; Junda Li; Dongjie Zhou; Wei Zhang; Tian’an Wang; Wei Li (International Journal of Engineering and Technology Innovation, 2025)
With the increasing number of decommissioned charging piles, efficient reuse of their components is essential for sustainable resource utilization and intelligent grid management. To address the challenges in recycling and scheduling retired charging pile components, this study proposes a cost-optimization approach for delivery planning in smart grid logistics. An Electric Vehicle Routing Problem with Time Windows (EDVRP-TW) model is formulated that considers vehicle capacity and time constraints. To solve it, an Improved Chicken Swarm Optimization Algorithm (ICOOT) is developed, integrating Circle chaotic mapping, spiral search strategy, and normal cloud mutation to enhance convergence speed and solution quality. Simulation experiments using real-world datasets demonstrate that the proposed method significantly reduces operation and maintenance costs, achieving up to an 11.77% cost reduction. The results validate the effectiveness and applicability of the model and algorithm in intelligent recycling and scheduling of grid materials.